Tác động của thanh khoản thị trường tài chính đến thanh khoản ngân hàng thương mại tại Việt Nam - Phạm Thị Hoàng , Anh; Lại Thị Thanh , Loan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The research aims to evaluate the impacts of market liquidity on liquidity reserve of commercial banks in the country which has a bank-based financial system. Based on panel data of 20 Vietnam commercial banks during the 2007–2017 period, the paper finds empirical evidence that an increase in market liquidity will lead to a decrease in reserve ratio of liquid assets to total assets. Interestingly, in similar financial market conditions, the paper suggests that state-owned banks prefer to keep more liquid assets than commercial joint-stock banks in Vietnam in spite of an increase in operating cost. In addition, by employing a random regression panel model, bank profitability is found to have a significant positive impact on liquidity to asset ratio at commercial banks. Besides, inflation is the only macroeconomic indicator that results in an increase in bank liquidity in Vietnam.
Keywords: Liquidity; Financial market; Commercial bank; Vietnam